Key audit matters for production-to-order industry and conservatism - Chang-yeol In; Taeheung Kim; Sambock Park (International Journal of Financial Studies, 2020)
In this study, the effects of key audit matters (KAMs), one of the measures recently introduced to improve accounting transparency in the production-to-order industry in terms of corporate sustainability, are examined. After the introduction of KAMs, auditors should publicly disclose key audit matters that had been internally judged in the past. In cases where these are missing or misunderstood, the range of the audito's liability may increase. Thus, from the viewpoint of the auditor, the description of KAMs can be recognized as the disclosure of internal judgments and an increase in the risk of litigation. It is judged that, to this end, auditors will perform their auditing work more conservatively in cases where they should describe KAMs. The results of analysis of companies to which KAMs are applied indicate that auditors carried out audits more conservatively for such companies. As such, the result can be interpreted as indicating that, due to the introduction of KAMs, auditors evaluate their risk highly and carry out audits more conservatively in order to reduce the risk. This study is meaningful in that it empirically analyzes the effects of the introduction of the recently implemented KAMs. In addition, this study provides implications for enterprises that prepare financial statements, supervisory institutions that conduct supervision, auditors, and capital market participants, as it presents the finding that, with the introduction of KAMs, auditors perform their work with more conservative perspectives. In addition, the findings of this study provide a basis for future studies on KAMs.
Keywords: M41; M42; 330; auditors; conservatism; Key audit matters (KAMs); production-to-order industry